Current approaches to assessing the degree of perinatal risk - N. A. Stetsenko; I. B. Fatkullina; L. A. Fayzullina; A. Yu. Lazareva; D. A. Fatkullina; D. G. Sitdikova (IRBIS LLC, 2022)
Aim: to study the factors leading to adverse perinatal outcomes allowing, on this basis, to predict degree of perinatal risk.Materials and Methods. The medical records of 155 patients who performed delivery in 2019-2021 were retrospectively analyzed. The following groups were formed: main group included 56 patients with adverse perinatal outcomes (9 fetuses died antenatally, 36 fetuses born below Apgar score 5, 9 newborns died within the first 168 hours of extrauterine life, 2 infant deaths). The control group included 99 patients with favorable perinatal outcomes. While assessing the data retrieved from medical records, sociobiological and laboratory-instrumental indicators, obstetric-gynecological and somatic anamnesis, the presence of extragenital pathology, the delivery process, information related to child condition at the time of birth and in early neonatal period were analyzed.Results. In patients of the main group, significant differences were revealed compared to control group, respectively: high parity (3 or more deliveries) - 11 (19.6 %) and 15 (15.1 %) (p = 0.001); vomiting of pregnant women in early gestation - 27 (48.2 %) and 14 (14.1 %) (p = 0.005); the presence of uterine scar after two or more caesarean sections - 7 (12.5 %) and 2 (2.1 %) (p = 0.009); former abortions - 24 (42.8 %) and 16 (16.1 %) (p = 0.0017); acute respiratory viral infection in the first trimester - 21 (37.5 %) and 13 (13.1 %) (p = 0.005); threatened abortion in the second trimester - 23 (41.0 %) and 15 (15.1 %) (p = 0.0005); Doppler-based blood flow disorders in the second trimester - 17 (30.3 %) and 11 (11.1 %) (p = 0.008) and in the third trimester - 9 (16.0 %) and 3 (3.0 %) (p = 0.006); altered amniotic fluid index according to ultrasound data in the second trimester - 6 (10.7 %) and 1 (1.0 %) (p = 0.011); intrauterine growth retardation in the third trimester - 15 (26.7 %) and 4 (4.0 %) (p = 0.012); severe preeclampsia - 6 (10.7 %) and 1 (1.0 %) (p = 0.04). In patients of the main group, pregnancy was finished prematurely in 41.1 % of cases compared to 100% term delivery in control group.Conclusion. The risk factors identified, which were manifested in the first and second trimesters of pregnancy may be predictors for adverse perinatal outcomes. Based on the study results for patients of the main and control groups, it was convinced that the topic of predicting favorable and unfavorable perinatal outcome is currently far from being disclosed, which is a long meticulous path of search, analysis and comparison.